PENERAPAN COOPERATIVE LEARNING TERHADAP KECERDASAN INTERPERSONAL SISWA PADA PEMBELAJARAN IPAS SEKOLAH DASAR - Novi Yunita; Mastiah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
In a school environment, interpersonal intelligence is important, because the space of relationships and communication will never be separated from daily activities. Based on the results of interviews with the homeroom teacher of grade V at SD Negeri 01 Kota Baru, it shows that there are still some students who still have low interpersonal intelligence. This study was conducted to determine significant differences in students' interpersonal intelligence in the experimental class and the control class. The approach used was quantitative with a quasi-experimental research type with a posttest-only non-equivalent control group design. The sampling technique used was saturated sampling with 47 students from two grades of SD Negeri 01 Kota Baru as the control and experimental groups. Data collection used a questionnaire. Based on the results of the calculation of the questionnaire scores for Interpersonal Intelligence in the control class and the experimental class, the average value (mean) in the control class was 68.97 while the average value (mean) in the experimental class was 72. Then, an analysis was carried out using the Shapiro-Wilk normality test and the Livene's homogeneity test. After the data were normally distributed and homogeneous so that the T-test requirements were met, the hypothesis test was carried out using the Independent Samples T-Test. The test results showed a significance value of 0.165 > 0.05, which indicates that there was no significant difference in interpersonal intelligence in the experimental class that was given cooperative learning treatment with the control class that used conventional learning in science learning.